Antarctic krill (Euphausia superba) oil high internal phase emulsions improved the lipid quality and gel properties of surimi gel - Lv, Yinyin; Sun, Xiaosong; Jia, Hui; Hao, Ruoyi; Jan, Mráz; Xu, Xianbing; Li, Shengjie; Dong, Xiuping; Pan, Jinfeng (Food chemistry, 2023)
In the study, high internal phase emulsions (HIPEs) prepared from Antarctic krill oil (AKO) were added into surimi and the effects on gel properties, lipid quality and stability were investigated. It is found that HIPEs-added groups exhibited higher gel strength and lower cooking loss than Oil-added counterparts. HIPEs-added groups had higher proportion of capillary water, and microstructure of HIPEs-added gels showed fewer large voids and small size droplets. HIPEs-added groups also showed less pronounced myosin heavy chain band. HIPEs- and Oil-added gels showed > 3500 mg/kg EPA + DHA and 0.4-0.8 mg/kg astaxanthin, and most HIPEs-added groups had higher levels of them but lower TBARS values. Results suggest AKO-HIPEs could reduce the intervention by lipids on myosin crosslinking during gelation, and protect fatty acids and asxtanthin from oxidation due to oxygen-isolation led by their high accumulation. Thus, AKO-HIPEs can be applied to fortify ω-3 PUFA and maintain good gel properties in surimi product.
Keywords: emulze; Emulsions; mastné kyseliny; Fatty Acids, Omega-3; Fatty Acids; High internal phase emulsion; ω-3 PUFA; Gels; gely; zvířata; Euphausiacea; omega-3 mastné kyseliny; Surimi; TBARS; Antarctic krill oil; Animals